Food And Beverage Business Innovation In Higher Education Environments: SWOT Analysis And Digital Literacy Empowerment - Sutomo Sutomo; Imam Mukhlis (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Food and Beverage (F&B) businesses in universities, especially at STIE and STIKES ABI Surabaya, face global challenges such as changing consumption patterns and global competition, while also adapting to unique dynamics at the local level. Ideally, F&B businesses at STIE and STIKES ABI Surabaya need to integrate business innovation by utilizing the potential of the university environment as a base for creativity and collaboration. Innovative business strategies include response to global and local changes, technology integration, and sophisticated marketing. This research fills the knowledge gap with a focus on business innovation, SWOT analysis, and digital marketing literacy in higher education F&B business. The novelty of the study lies in a comprehensive approach to these key aspects, unearthing innovative solutions to overcome challenges and capitalizing on opportunities in the college culinary market. The positive implications involve increasing business competitiveness, local economic growth, and contributing to sustainable development, providing practical guidance for F&B business people in the college environment. This study used a descriptive qualitative approach. The subject of the study involved the owner and employees of the canteen. Data was collected through observation, interviews, and documentation. Data analysis involves the reduction, display, and inference of data, with tringulation used to ensure validity. The research location focused on the two canteens in the college. The results showed that canteen owners at STIE ABI Surabaya and STIKES ABI Surabaya adopted innovative business strategies through SWOT Analysis and digital marketing literacy. The integration of SWOT Analysis and digital literacy allows for menu customization and quick response to changes in campus trends or policies. In conclusion, the combination of these strategies provides a strong foundation for innovative businesses, increases competitiveness, and strengthens sustainability in the campus environment